Cytotoxic Activity and Lymphocyte Subtypes in Mice Selected for Maximal and Minimal Inflammatory Response after Transplantation of B16F10 and S91 Melanoma Cells - Castoldi, Lindsey; Romagnoli, Graziela Gorete [UNESP]; De Assis Golim, Marjorie [UNESP]; Ribeiro, Orlando Garcia; Martinez Ibañez, Olga Célia; Maria, Durvanei Augusto; Pinto Domeneghini, Andréa Vanessa; Gameiro, Maria Carolina [UNESP]; Martins, Priscila Raquel [UNESP]; Mischan, Martha Maria [UNESP]; Kaneno, Ramon [UNESP] (Hindawi, 2022)
AIRmax and AIRmin mice strains were selected according to the intensity of their acute inflammatory responsiveness. Previous studies have shown that AIR mice differ in their resistance to chemically induced skin tumors and in the development of melanoma metastases, in addition to differences in neutrophil and NK cells activity. In the present work, we aimed to evaluate whether the difference of susceptibility to murine melanoma is associated with NK cytotoxic activity against Yac.1 cells and lymphocyte subsets. Mice were subcutaneously inoculated with B16F10 or S91 melanoma cells. After 7, 14, or 30 days, the animals were euthanized to analyze the number of lymphocyte subsets, cytotoxic activity, and number of cytokine-producing spleen cells. AIRmax mice presented a higher number of CD4+/CD25+ cells than that of AIRmin mice following inoculation of B16F10 cells, whereas inoculation of S91 cells reduced CD4+/CD25+ and increased TCD8+ cell subsets in the AIRmax mice. AIRmax mice had a higher number of interleukin (IL)-10- and IL-12-producing cells and a lower number of interferon-γ-producing cells than those of AIRmin mice at 30 days. The cytotoxic activity of nonadherent spleen cells was similar in both the AIR strains. These results suggest that melanoma cells can induce different responses in AIR mice, possibly owing to alterations in regulatory mechanisms, such as the action of CD4+/CD25+ regulatory T cells and IL-10, in AIRmax mice.